Prognostic scores for predicting overall survival in patients with metastatic renal and urothelial cancer undergoing immunotherapy: which one to use? - Walach, Margarete; Burger, Ralph; Brumm, Felix; Nitschke, Katja; Wessels, Frederik; Nuhn, Philipp; Worst, Thomas; Hardenberg, Jost von; Grüne, Britta; Jarczyk, Jonas (World journal of urology, 2025)
Evaluation of the prognostic significance of four different scoring systems in a real-world cohort of patients with metastatic urothelial carcinoma (mUC) or renal cell carcinoma (mRCC) undergoing immunotherapy (IO).